Aritmética simbólica temprana y habilidades motoras gruesas, finas y perceptuales en niños preescolares mexicanos (Early symbolic numeracy and gross, fine, and perceptual-motor skills in Mexican preschool children) - Benavides Pando, Elia Verónica; Jiménez Lira, Carolina; Paz García, Daniel Susana; Susperreguy, María Inés; Palma Gardea , Lucia Consepción; Mondaca Fernández, Fernando (Retos, 2024)
La relación entre las habilidades numéricas tempranas y las habilidades motoras se ha examinado previamente, sin embargo, se han obtenido diferentes resultados dependiendo de si se consideraron las habilidades motoras gruesas, finas o perceptivo-motoras en el estudio, y de las variables dependientes (habilidades numéricas) que se analizaron. El objetivo de la presente investigación fue examinar la relación entre el desempeño de niños en edad preescolar en dos evaluaciones de habilidad numérica simbólica y la motricidad gruesa, fina y perceptivo-motriz. Un total de ciento veintitrés niños mexicanos en edad preescolar fueron evaluados en sus habilidades motoras gruesas, finas y perceptivo-motoras, sus habilidades numéricas (es decir, resolución de problemas aplicados y comparación numérica simbólica) y sus habilidades precursoras de matemáticas (es decir, identificación de números, cardinalidad y conteo verbal), control inhibitorio y memoria de trabajo visoespacial. Los resultados de las regresiones lineales jerárquicas mostraron que la resolución de problemas aplicados fue predicha solo por las habilidades precursoras de matemáticas, mientras que la capacidad de comparar dos números simbólicos fue predicha significativamente solo por las habilidades perceptivo-motoras. El estudio destaca la importancia de las habilidades perceptivo-motoras para el aprendizaje temprano de las matemáticas en los niños.Palabras clave: Habilidades numéricas tempranas; habilidades motrices; habilidades perceptivo-motoras; niños de preescolar.Abstract. The relation between early numeracy and motor skills has previously been examined, however, different results have been obtained depending on whether gross, fine, or perceptual-motor skills were considered in the study and the numeracy outcomes that were analyzed. The goal of the present research was to examine the relation between preschool children’s performance on two assessments of symbolic numeracy and gross, fine, and perceptual-motor skills. A total of one-hundred-and-twenty-three Mexican preschool children were assessed on their gross, fine, and perceptual-motor skills, their numeracy skills (i.e., applied problem-solving and symbolic number comparison) their numeracy precursor skills (i.e., number identification, cardinality and verbal counting), inhibitory control and visual-spatial working memory. Results from hierarchical linear regressions showed that applied problem-solving was predicted only by children’s numeracy precursor skills while the ability to compare two symbolic numbers was significantly predicted only by perceptual-motor skills. The study highlights the importance of perceptual-motor skills to children’s early numeracy learning.Keywords: Early numeracy skills; motor skills; perceptual-motor skills; preschool children.Abstract. The relation between early numeracy and motor skills has previously been examined, however, different results have been obtained depending on whether gross, fine, or perceptual-motor skills were considered in the study and the numeracy outcomes that were analyzed. The goal of the present research was to examine the relation between preschool children’s performance on two assessments of symbolic numeracy and gross, fine, and perceptual-motor skills. A total of one-hundred-and-twenty-three Mexican preschool children were assessed on their gross, fine, and perceptual-motor skills, their numeracy skills (i.e., applied problem-solving and symbolic number comparison) their numeracy precursor skills (i.e., number identification, cardinality and verbal counting), inhibitory control and visual-spatial working memory. Results from hierarchical linear regressions showed that applied problem-solving was predicted only by children’s numeracy precursor skills while the ability to compare two symbolic numbers was significantly predicted only by perceptual-motor skills. The study highlights the importance of perceptual-motor skills to children’s early numeracy learning.Keywords: Early numeracy skills; motor skills; perceptual-motor skills; preschool children.